Study of the biota of laboratory rats: characterization of commensal Escherichia coli - Vega-Manriquez, Xochitl (2022)
The aim if this study was to characterize strains of E. coli isolated from Rattus norvegicus belonging to a level 1 animal facility. Faecal samples were taken from 13 rats. Five colonies were randomly selected from the primary growth of the culture of each sampled individual. Biochemical tests were performed and the pathotype and phylogroup were established in the strains that were identified as E. coli by means of the PCR technique. In addition, tests for biofilm formation and antimicrobial susceptibility were performed. Results showed that 65% (26/40) of the isolated strains corresponded to E. coli and all clustered in phylogroup B2. Six of the E. coli strains were resistant to nitrofurantoin (23%), four were resistant to ampicillin (15%), and three strains were resistant to cefozolin (11%). None showed the formation of biofilms, nor the amplification of genes related to any pathotype. The results denote that E. coli belonging to the biota of laboratory rats presents resistance to antibiotics and the presence of the chuA and yjaA genes associated with the B2 phylogroup strains related to extraintestinal diseases.